Study of Clinical Profile in Nontraumatic Adult Patients with Altered Sensorium and Its Correlation with The Outcome at Emergency Room of a Tertiary Care Hospital, Devdaha, Rupandehi - Gaira, Manoj; Darlami, Babita laxmi; Chettri, Sahas; Pandey, Usha Kiran; Koirala, Diwakar (Medical Journal of Eastern Nepal, 2026)
Background Altered sensorium accounts for approximately 4–10% of all emergency visit presentations worldwide, posing a major challenge to emergency doctors. At Devdaha Medical College and Research Institute (DMCRI), 115 non-traumatic adult cases were studied. Early clinical assessment helps timely management and predicts outcomes. Objectives This study aimed to assess the clinical profile and outcome assessment (mortality, morbidity) of non-traumatic patient of altered sensorium. Methods This prospective observational hospital-based study was conducted in the emergency department of DMCRI from April to September 2025. Adult patients (≥18 years) with non-traumatic altered sensorium were included. Data were collected using questionnaire, analyzed using descriptive statistics, including frequency, percentage, and range. Convenience sampling was used after ethical approval (Reference No: 1924/o81/082). Results In 115 patients (age 18–83 years), 64 (55.6%) were male. Most patients (n = 33, 28.6%) were aged 61–70 years. Common presenting complaints were headache (77.3%), nausea / vomiting (70.4%) and focal neurological deficit (61.7%). Cerebrovascular accident (CVA) was the commonest cause (n = 38, 33%), followed by metabolic disorders (n = 29, 25.2%) and substance-related intoxication (n = 24, 20.9%). Overall mortality was 20% (n = 23); mortality was highest among metabolic causes (47.8% of deaths), followed by CVA (21.7%) and substance poisoning (13%). At discharge, 48 (41.7%) patients had complete recovery and 44 (38.2%) had residual disability. Conclusions Altered sensorium predominantly affected elderly patients, with stroke and metabolic disturbances. Early recognition helps to reduce poor outcome. Strengthening emergency and inpatient care can significantly improve outcomes.